PELESTARIAN RUANG TERBUKA HIJAU TINGKAT KELURAHAN MELALUI PROGRAM KULIAH KERJA NYATA UNIVERSITAS COKROAMINOTO YOGYAKARTA - Hamidah, Diana Rofi; Winarni, Harti (Universitas Cokroaminoto Yogyakarta, 2024)
Community Service Program is a mandatory activity which should be done by students of Yogyakarta Cokroaminoto University. Thematic Community Service Program were done in Gambiran Village, Pandeyan Urban Village, Umbulharjo District of Yogyakarta. This program was held since 6th of February – 21st of March 2023. Community Service Program was started from location survey, village and university party consultation, until the ongoing program of Community Service. The programs were consisted of individual programs as well as group programs. The results of the programs were environmental and cultural conservation also community empowerment sustainability. Community Service Program becomes a facility of learning and practicing for students. Besides, through Community Service Program, Cokroaminoto University can contribute to the giving of education value as well as humanity value outside campus. One of the contributions happened was the conservation of Legawong Park. This park was an embodiment of open green space where community can take advantage of it. Conservation and maintenance became the solution for Gambiran Village’s open green space. It is hoped that this program not only becomes the transfer of knowledge but also transfer of value to the more positive way.